Stop Kekerasan Seksual dengan Pendidikan Anak Sejak Dini - Nabila Muthia Rezky Maghfirah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
Child sexual violence is a serious issue that continues to increase in Indonesia, with profound impacts on the social, psychological, and physical development of children. This study aims to explore the role of early sexual education as a preventive measure in overcoming child sexual violence. The research method used is a literature study, by collecting data from various reliable sources, such as journals, books, and research reports. The results of the study indicate that sexual education provided to children from an early age can improve their understanding of the body, the right to privacy, and how to protect themselves from inappropriate actions. This education can also equip children with knowledge of moral and ethical values ​​that are relevant to their social interactions. The implications of this study are the importance of the role of parents, teachers, and the environment in providing appropriate and ongoing sexual education in order to create a safe environment and protect children from the risk of sexual violence.